MAPPING THE HABITS OF MIND OF PRE-SERVICE BIOLOGY TEACHER STUDENTS IN SUPPORTING EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Thinking habits can be cultivated through habits of mind (HoM), shaping pre-service teachers’ analytical, reflective, and decision-making skills essential for Education for Sustainable Development (ESD). This study examines HoM proficiency among 99 pre-service biology teachers using closed- and open-ended questionnaires and curriculum analysis. More than half of pre-service biology teachers scored moderately, indicating a need for habits of mind improvement. The findings offer educators, curriculum developers, and policymakers insights into designing strategies to strengthen HoM, ensuring teachers can integrate sustainability concepts into education, a task of significant urgency and importance. By fostering critical inquiry, problem-solving, and lifelong learning, prospective teachers will better prepare students to address the global sustainability challenge.
Keywords: habits of mind; biology teacher education; ESD; sustainability competencies